Is Almond Consumption More Effective Than Reduced Dietary Saturated Fat at Decreasing Plasma Total Cholesterol and LDL-c Levels? A Theoretical Approach - Rudy M. Ortiz; Steven Garcia; Arnold D. Kim (Journal of Nutrition and Metabolism)
Hypercholesterolemia can be a consequence of excessive dietary saturated fatty acid (SFA), while almond-supplemented diets can improve lipid profiles. However, the differential and independent impacts of dietary SFA and almondsupplemented diets on plasma total cholesterol (pTC) and low-density lipoprotein (pLDL-c) concentrations have not been directly compared and are not well described. We reviewed the available data to construct multiple regression analyses to theoretically assess the impact of relative almond intake (RAI) and dietary SFA on reducing pTC and pLDL-c concentrations. Strong, negative correlations between RAI and percent change in mean pTC (R=0.776;P=0.005) and RAI and percent change in mean pLDL-c (R=0.818;P=0.002) were detected. The relationships between percent change in mean dietary SFA, and percent change in mean pTC and mean pLDL-c were weaker and only significant for pLDL-c. The multiple regression analyses demonstrated modest improvements in the strength of the correlations for both pTC (R=0.804;P=0.016) and pLDL-c (R=0.855;P=0.005). The models suggest that the increase in RAI contributes to the reduction in pTC and pLDL-c to a greater extent than a reduction in dietary SFA, but a simultaneous decrease in dietary SFA should further improve lipid profiles.